Beberapa Teori Dan Aplikasi Rumus Thornthwaite Untuk Menghitung Jumlah Cadangan Sumberdaya Air = Some theories and aplication of the Thornthwaite formula to estimate water resource potential - Nugroho, Amien Nugroho (Majalah Geografi Indonesia, 1989)
The aim of this paper is to introduce the aplication of Thornthwaite formula in stimating the potential of water resources in a certain part of Yogyakarta Special Region. By using the climatological data of that area, quantitatively the water resource potential can be immediately calculated and recognized. In this study, Parangtritis and its surroundings, were used as a model. Calculation of the water resource potential results in an average value of the water resource potential of 1,2 - 2 x 106 m3 /12,,n22 /year